ACTIONS AND DECISIONS OF THE COURT IN PREPARING THE CASE AND COMPLAINTS FOR CHECKING ON APPEAL - N. N. Mazina (Russian Journal of Economics and Law)
Objective: basing on the study of appellate procedure for verification of judicial decisions in the Russian criminal process and the legal analysis of the criminal procedure: 1) to research the system of actions and decisions of the court in preparing the case and complaints for checking on appeal, and the problems encountered by legal practitioners at this stage of the criminal proceedings; 2) to develop a series of proposals aimed at improvement of this institution. Methods: the research is based on the universal dialectical method of cognition, the method of comparison, the formal-legal and specific and private law research methods. Results: basing on the analysis of current legislation and practice, the author draws attention to the fact that the law wording, according to which the studied measure of restraint is chosen for the convicted "...until the sentence comes into legal force", leads to uncertainties in the legal status of prisoners. Moreover, the lack of the specific date in the sentence, for which the measure is established, deprives prisoners of the opportunity to put forward the questions of legality and validity of a very long and almost uncontrollable detention. The author insists on returning to the procedure for mandatory discussion of this issue in preparing the case for appeal in a court session, ensuring the rights of all stakeholders. Scientific novelty: it should be noted that in the Russian criminal procedure doctrine and enforcement does not fully take into account the changes in procedural form of the updated appeal inspections introduced by Federal Law No. 217-FZ of 23.07.201315, which clearly indicate strengthening of the public principles the appeal procedure. Therefore, there is a need for more integrated and comprehensive study of both the norms of Chapter 45.1 of the Russian Criminal-Procedural Code16 (CPC), and patterns of the current practice of their application. The results of the study should provide the necessary methodological framework to develop recommendations on improving the legal regulation of this form of judicial protection, a means of optimization of the practical side of the updated appeal proceedings in the Russian criminal procedure. Practical value: the theoretical findings formulated in the study can and should be used in scientific, legislative and practical judicial activities in order to create the optimal form of the new appeal procedure.